Child health and living at high altitude. Issue 10 (9th December 2008) - Niermeyer, S; Andrade Mollinedo, P; Huicho, L
Abstract : The health of children born and living at high altitude is shaped not only by the low-oxygen environment, but also by population ancestry and sociocultural determinants. High altitude and the corresponding reduction in oxygen delivery during pregnancy result in lower birth weight with higher elevation. Children living at high elevations are at special risk for hypoxaemia during infancy and during acute lower respiratory infection, symptomatic high-altitude pulmonary hypertension, persistence of fetal vascular connections, and re-entry high-altitude pulmonary oedema. However, child health varies from one population group to another due to genetic adaptation as well as factors such as nutrition, intercurrent infection, exposure to pollutants and toxins, socioeconomic status, and access to medical care. Awareness of the risks uniquely associated with living at high altitude and monitoring of key health indicators can help protect the health of children at high altitude. These considerations should be incorporated into the scaling-up of effective interventions for improving global child health and survival.